PERTANGGUNGJAWABAN SOSIAL PABRIK ROKOK ALAINA DITINJAU DARI ETIKA BISNIS ISLAM (An-Nisbah: Jurnal Ekonomi Syariah, 2015)
The background of this study because at Ngantru’s region there is one pesantren’s, there is one effort which is Alaina’s Smoke Factory.  Smoke Factory is one effort which of course it have good social impact that impacted big, be or little even but that it must each effort which walk and amends of course it performs to form social responsibility to surrounding society. The type of study is feld research using qualitative and desdriptive approach. The result of this studi is Alaina’s Smoke Factory make do corporate social responsibility, there are responsibility to God,  responsibility to Nature and responsibility to other people. The type is sector religion, healthy sector and economi sector. Example to give work with recrutmen people and santri,  faith job and other social job to welfare employee and people’s.Keywords: Social Responsibility, Islamic Business Ethic